2007
DOI: 10.1007/s10531-007-9213-3
|View full text |Cite
|
Sign up to set email alerts
|

Deforestation and biodiversity: effects of bushland cultivation on dung beetles in semi-arid Tanzania

Abstract: Dung beetles provide important ecosystem services in the habitats where they occur. The activity of dung beetles enhances soil nutrient cycling and increases the soil's ability to absorb and hold water. Consequently, these beetles are particularly important in semi-arid environments. This study analyses the importance of remaining wooded habitat patches (bushland) for the survival of a diverse dung beetle fauna in an otherwise cultivated landscape in semi-arid Tanzania. Dung beetles were sampled by pitfall tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
(53 reference statements)
1
2
2
Order By: Relevance
“…Ecotone shared species with forest and agriculture habitat, and least similarity existed between forest and agriculture habitat. Similarity in species composition and abundance between forest and ecotone is in contrast to results of earlier studies done across a forest-savanna ecotone in Bolivia (Spector and Ayzama, 2003), forest-cerrado ecotone in Brazil (Duraes et al, 2005), bushland and agriculture habitat in Tanzania (Nielsen, 2007), forest-savanna edge and forest-roadside edge in French Guiana (Feer, 2008) and forest-pasture edges in Los Tuxtlas Biosphere Reserve (Diaz et al, 2010), where species composition and abundance varied between forest and edge with significant decrease in abundance observed in edge. Forest edges have a relatively higher temperature, lower humidity and is exposed to higher solar radiation when compared to forest interior and this impacts organisms (Kapos, 1989;Brown, 1993).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Ecotone shared species with forest and agriculture habitat, and least similarity existed between forest and agriculture habitat. Similarity in species composition and abundance between forest and ecotone is in contrast to results of earlier studies done across a forest-savanna ecotone in Bolivia (Spector and Ayzama, 2003), forest-cerrado ecotone in Brazil (Duraes et al, 2005), bushland and agriculture habitat in Tanzania (Nielsen, 2007), forest-savanna edge and forest-roadside edge in French Guiana (Feer, 2008) and forest-pasture edges in Los Tuxtlas Biosphere Reserve (Diaz et al, 2010), where species composition and abundance varied between forest and edge with significant decrease in abundance observed in edge. Forest edges have a relatively higher temperature, lower humidity and is exposed to higher solar radiation when compared to forest interior and this impacts organisms (Kapos, 1989;Brown, 1993).…”
Section: Discussioncontrasting
confidence: 88%
“…This is because the forests in the region is fragmented, this results in frequent incursions of long ranging herbivorous mammals such as elephant, gaur into forest edges and even agriculture habitats in the region. High species richness and Shannon-Weaver diversity in ecotone and agriculture habitat when compared to forest is in contrast to records from Borneo (Davis et al, 2001) (Nielsen, 2007), and Wayanad (Vinod, 2009). Studies have shown that increase in species richness in disturbed habitats is associated with species that respond positively to disturbance whereas stenotopic species adapted to closed canopy are negatively affected (Davis et al, 2001, Janzen, 1987.…”
Section: Discussioncontrasting
confidence: 70%
“…Similar observations were made in multiple studies done in modified habitats (Nichols et al, 2007). Cultivated land often lacks the microhabitat diversity of natural habitats and there are fewer dung types available due to the disappearance of large wild mammals (Nichols et al, 2007;Nielsen, 2007). Agriculture habitats in Nelliampat h i are relatively small patches amidst vast stretches of plantations and forests and though incursions of wild animals into agriculture habitat has been observed, still the diversity and amount of dung types available is less compared to the forest habitat, which in turn affected the abundance of dung beetles in agriculture habitat.…”
Section: Discussionsupporting
confidence: 67%
“…Thick under storey vegetation in these moist forests also act as a hindrance to ball rolling activities (Vinod, 2009). Their absence in agriculture habitat can be related to their sensitivity to changes in vegetation, microclimate and land use (Nielsen, 2007). Dwellers are strongly associated with large herbivore dung pads and breeds successfully only in undisturbed dung pads with little competition from competitively superior tunnelers and rollers (Hanski and Cambefort 1991;Krell et al, 2003;Krell-Westerwalbesloh et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of dung beetle communities between forests and more open vegetation (savannas, pastures or clear-cuts) have generally revealed almost complete dung beetle species turnover (Krell et al 2003;Spector & Ayzama 2003;Scheffler 2005;Nielsen 2007). Communities in open habitats, whether natural or anthropogenic, are often characterized by a hyper-abundance of few small-bodied species (Krell et al 2003;Nichols et al 2007;Navarrete & Halffter 2008).…”
Section: Introductionmentioning
confidence: 99%